Stand-alone hybrid energy systems for remote area power generation - Armin Razmjoo; Reza Shirmohammadi; Afshin Davarpanah; Fathollah Pourfayaz; Alireza Aslani (Energy Reports, 2019)
Energy accessibility especially electrical energy is considered as one of the most appealing factors to achieve energy sustainability. The purpose of this study is to investigate energy sustainability using renewable energies for two high potential cities in the south-east of Iran until the year 2030. In this regard, Homer software is used to evaluate economic and technical analyses of PV-wind-diesel hybrid system for the two cities by the data gathering which was collected from Iran's meteorological organization. Therefore, the average of solar radiation per month for Zabol and Zahak were about 9 and 9.1 (h/d). Also, mean wind speeds are calculated 5.35 m/s and 4.7 m/s for Zabol and Zahak respectively which proposed that these cities have high potential in order to electrical production by a hybrid system. Furthermore, the amount of electricity production by PV array for Zabol and Zahak were 1700 (kWh/yr) and 1669 (kWh/yr) respectively, and the amount of electricity production by wind turbine were 9036 (kWh/yr) and 7263(kWh/yr) for Zabol and Zahak respectively. Consequently, it is of elaborated that the investments on solar and wind energy sectors for both cities would be economically justified.
Keywords: 330; Hybrid energy technologies; Renewable energy; Solar energy; Technical-economic analysis; Wind energy